After-school Clubs: Fostering Protective Factors - Aarzoo; Shibal Bhartiya; Tarundeep Singh (Indian Journal of Social Psychiatry)
Background: Affiliation to gangs becomes analogous to the need for belongingness; a leader or member of the gang can substitute a primary caregiver, or act as a parent figure or a role model. Children and youth associated with gangs lean toward antisocial activities compared to their nongang counterparts. After-school clubs (ASCs) probably demote gang membership providing support in various aspects of self-growth and thereby compassing the need for affiliation. Objectives: The aim of the study was to assess the relationship between risky behavior and gang membership in children and compare the gender differences for the same. Materials and Methods: This cross-sectional, observational study was conducted using purposive sampling approaching the children enrolled in an ASC run for children who had dropped out of the school. The participants were 97 children (male and female) attending the ASC between the age range of 6–18 years. They were assessed on sociodemographic and academic profiles; Social, Academic, and Emotional Behavior Risk Screener (SAEBRS); and Gang Membership Inventory (GMI). Results: It was observed that the SAEBRS score range of female participants implied “not at risk,” while male participants scored “at risk” scores on social and emotional domains. On GMI, only male participants’ scores showed gang affiliation. The model explained that 76% of the variance in GMI was contributed by the SAEBRS. Conclusion: ASC contributed valuably in integrating a vulnerable population into the productive national mainstream. Affinity with ASC can enhance the protective factors and minimize the risk of gang membership. Studies in the future can explore parental factors and resilience of this population along with socioeconomic factors to delve into risky as well as protective behaviors.